36.6k views
5 votes
Solve: 10(3- x) + 2(x - 2) = 6(2x - 2)

User Luke Tan
by
5.9k points

2 Answers

4 votes
I think I know it.

First, you need to distribute the coefficients to the items in the ()'s

30-10x+2x-4=12x-4

Then you need to carry over the x's on one of the sides.

-10x+10x=0x
12x+10x=22x
2x-2x=0x
22x-2x=20x
30-4=20x-4

Then, move over the -4 to the other side. The point of this is to have all numbers on one side and all variables on the other side, while keeping the equation equal.

-4+4=0
You may want to do 30-4 first before doing the next step.
26+4=30

30=20x

Finally, divide 30 by 20

30/20=1.5

x=1.5

Therefore, X equals 1.5

I spent about 10 minutes on this answer. I really hope this helps!
User Clinton Pierce
by
5.7k points
4 votes
1 Expand
30−10x+2x−4=12x−12

2 Simplify 30−10x+2x−4 to 30−8x−4
30−8x−4=12x−12

3 Simplify 30−8x−4 to −8x+26
−8x+26=12x−12

4 Add 8x to both sides
26=12x−12+8x

5 Simplify 12x−12+8x to 20x−12
26=20x−12

6 Add 12 to both sides
26+12=20x

7 Simplify 26+12 to 38
38=20x

8 Divide both sides by 20
38/20=x

9 Simplify 38/20 to 19/10

10 Switch sides
x=19/10

Decimal Form: 1.9
User Peter MacPherson
by
5.7k points